PENGARUH E-SERVICE QUALITY DAN PERCEIVED VALUE TERHADAP CUSTOMER LOYALTY (SURVEI PADA PELANGGAN ONLINE RETAIL ALFACART DI JAWA BARAT) - Rury Nugraheni, - (2020)
At this time, the retail business in West Java continues to experience growth so rapidly. There are many types of retail business to develop, one of which dominates that of the retail business, a grocery / convenience store. The number of retail convenience store becomes a consideration for customers in making spending choices. Increasing competition between one store with another store requires the company to innovate in order to survive in the market. Shifting the shopping behavior of today's society who expect the convenience of shopping online has also become one of the solutions for the retail grocery / convenience store. Alfacart as one of the company O2O is required to continue to innovate and further strengthen the strategy in marketing, so that customer loyalty can be maintained. Customer loyalty can be created through the e-service quality and perceived value. This study aims to (1) an overview of e-service quality and perceived value on customer loyalty, (2) the influence of e-service quality on customer loyalty, (3) the influence of perceived value on customer loyalty, (4) the influence of e-service quality and perceived value towards customer loyalty. This type of research is descriptive verification. The method used is simple random sampling with sample size of 200 respondents. The analysis technique used is the analysis of Structure Equation Model (SEM) using the program AMOS 22 for Windows. The findings of this study indicate that e-service quality in the category good enough, perceived value is in the good category and customer loyalty in the category good enough. In this study also found that e-service quality and perceived value have positive and significant influence to customer loyalty. In an effort to increase customer loyalty towards e-service quality and perceived value, the company must constantly improve the quality both in terms of innovation sites and applications, better service to every consumer, as well as holding special offers periodically. So the expected e-service quality and perceived value can be considered more and controlled directly by the company in improving customer loyalty.